Synergy Between the Credibility Revolution and Human Development in Africa - Adetula, Adeyemi; Forscher, Patrick; Basnight-Brown, Dana; Azouaghe, Soufian; Ouherrou, Nihal; Charyate, Abdelilah; Hansen, Nina; Adetula, Gabriel, Agboola; IJzerman, Hans (My University, 2021)
Spurred by a crisis in their confidence in past findings, psychology in North America, Europe, and Australia has been undergoing a credibility revolution, which has spurred the development and popularization of open science practices to improve the research process. Alongside this development, a broad array of stakeholders have noted that African science is at its own crossroads, as investments in this sector can facilitate human development on the continent. Here we argue that these two movements can facilitate each other: psychology in North America and Europe can benefit from stronger psychology research communities on the African continent, while African scientists can benefit from credible evidence generated through open, freely-available open science practices and tools. However, this synergy will only materialize if a wide array of stakeholders invest in African science through providing resources, training, and specially adapted research tools while simultaneously avoiding ethical pitfalls such as corruption and research colonialism.
Keywords: Africa; corelab; Credibility revolution; Generalizability; Open science; Open science Africa; open science initiatives; Psychological science; Psychology